Anammox sludge preservation: Preservative agents, temperature and substrate. (1st June 2022) - Huang, Dong-Qi; Wang, Ye; Wu, Qian; Chen, Jin-Rong; Li, Zi-Yue; Fan, Nian-Si; Jin, Ren-Cun
Abstract: The difficulties of enrichment and preservation of anaerobic ammonium oxidation bacteria (AnAOB) greatly limit their application in practice. Herein, traditional and emerging preservative agents (e.g., EPS + N2 H4, betaine, glycerol and trehalose) were evaluated for their preservation of AnAOB-dominant sludge at different temperatures (e.g., 4 °C and room temperature). In addition, the effects of substrates on preservation were also considered. The results showed that adding betaine or glycerol at 4 °C was the optimal strategy for preserving anammox granular sludge. The relative anammox activities (rAA) increased by 145.26% and 158.30% at the recovery phase, respectively. Moreover, the absolute abundances of functional gene hzs A increased by 339% and 46%, respectively. Although the granular properties and microbial community structures changed during the preservation, the general performance of anammox granules could effectively restored. Collectively, this study provides the optimal strategies for anammox sludge preservation at low temperatures. Graphical abstract: Image 1 Highlights: Preservation with betaine or glycerol at 4 °C was optimal for the anammox sludge. The addition of both preservation agents led to a better recovery performance. The absolute abundances of hzs A and nir S increased after the recovery phase. The relative abundance of Denitratisoma also showed an increasing tendency.